(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
The quality of gamma irradiated climbing perch was assessed in respect of sensory (organoleptic score), biochemical (TMA and TVN) and microbiological (TBC, TMC, TYC, TCC and Salmonella) tests. Two different doses of gamma irradiation (2 kGy and 6 kGy) were applied while preserving at -20°C. The quality changes were observed for 60 days storage period at six time intervals (1, 7, 15, 30, 45 and 60 days). It was found that the quality of all fish deteriorated with the progress of storage period. The values of all the parameters assessed were higher in non-irradiated fish than that of irradiated fish. No significant differences were observed among the parameters of Thai and Indigenous strain. The most desirable condition for both strains was found in samples treated with 6 kGy irradiation. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15608 J. Asiat. Soc. Bangladesh, Sci. 38(2): 183-188, December 2012